DIURETIC USE AND RISK OF VERTEBRAL FRACTURE IN WOMEN - Paik, Julie M. (Am J Med, 2016)
BACKGROUND: Vertebral fracture is the most common type of osteoporotic fracture. While thiazide diuretics, which are commonly prescribed for the treatment of hypertension, decrease calciuria, they may also induce hyponatremia, which has been associated with increased vertebral fracture risk. Loop diuretics increase calciuria, which would reduce bone mineral density and increase vertebral fracture risk, but they rarely cause hyponatremia. Recent studies on diuretics and fractures did not include or specifically examine vertebral fracture. The few studies of diuretics and vertebral fracture have been limited by cases defined by self-report or administrative data, relatively small number of cases, study design that was not prospective, and lack of long-term follow-up with updated information on diuretic use. METHODS: We conducted a prospective cohort study of thiazide diuretic use, loop diuretic use, and risk of incident clinical vertebral fracture in 55,780 women, 55–82 years of age, participating in the Nurses’ Health Study, without a prior history of any fracture. Diuretic use was assessed by questionnaire every four years. Self-reported vertebral fracture was confirmed by medical record review. Cox proportional-hazards models were used to simultaneously adjust for potential confounders. RESULTS: Our analysis included 420 incident vertebral fracture cases documented between 2002 and 2012. The multivariate-adjusted relative risk of clinical vertebral fracture for women taking thiazides compared with women not taking thiazides was 1.47 (95% CI 1.18 to 1.85). The multivariate adjusted relative risk of vertebral fracture for women taking loop diuretics compared with women not taking loop diuretics was 1.59 (95% CI 1.12 to 2.25). CONCLUSION: Thiazide diuretics and loop diuretics are each independently associated with increased risk of vertebral fracture in women.